Ukrainian chocolate market research - Ivanova, Zhanna; Vlasenko, Ludmila (My University, 2014)
The chocolate confectionery sector is one of the most active and fastest- developing markets. Sales growth has been influenced by growth in the overall economy, urbanization, and an increasingly organized retail market. Ukrainian consumers in urban areas are looking for more convenient stores with better prices, products and services. Market reforms and challenges of Ukrainian market also brought a significant change in the assortment, appearance and quality of food products over the past seven or eight years.
Keywords: quality of food products; market chocolate; confectionery sector; якість продуктів харчування; ринок шоколаду; кондитерська галузь; качество продуктов питания; рынок шоколада; кондитерская отрасль; кафедра ділової іноземної мови та міжнародної комунікації